Isolation of an Anti–tumour Disintegrin: Dabmaurin–1, a Peptide Lebein–1–like, from Daboia mauritanica Venom - Florence Chalier; Laura Mugnier; Marion Tarbe; Soioulata Aboudou; Claude Villard; Hervé Kovacic; Didier Gigmes; Pascal Mansuelle; Harold de Pomyers; José Luis; Kamel Mabrouk (Toxins, 2020)
In the soft treatment of cancer tumours, consequent downregulation of the malignant tissue angiogenesis constitutes an efficient way to stifle tumour development and metastasis spreading. As angiogenesis requires integrin−promoting endothelial cell adhesion, migration, and vessel tube formation, integrins represent potential targets of new therapeutic anti−angiogenic agents. Our work is a contribution to the research of such therapeutic disintegrins in animal venoms. We report isolation of one peptide, named Dabmaurin−1, from the hemotoxic venom of snake Daboia mauritanica, and we evaluate its potential anti−tumour activity through in vitro inhibition of the human vascular endothelial cell HMECs functions involved in tumour angiogenesis. Dabmaurin−1 altered, in a dose−dependent manner, without any significant cytotoxicity, HMEC proliferation, adhesion, and their mesenchymal migration onto various extracellular matrix proteins, as well as formation of capillary−tube mimics on MatrigelTM. Via experiments involving HMEC or specific cancers cells integrins, we demonstrated that the above Dabmaurin−1 effects are possibly due to some anti−integrin properties. Dabmaurin−1 was demonstrated to recognize a broad panel of prooncogenic integrins (αvβ6, αvβ3 or αvβ5) and/or particularly involved in control of angiogenesis (α5β1, α6β4, αvβ3 or αvβ5). Furthermore, mass spectrometry and partial N−terminal sequencing of this peptide revealed, it is close to Lebein−1, a known anti−β1 disintegrin from Macrovipera lebetina venom. Therefore, our results show that if Dabmaurin−1 exhibits in vitro apparent anti−angiogenic effects at concentrations lower than 30 nM, it is likely because it acts as an anti−tumour disintegrin.